2020
DOI: 10.1080/21505594.2020.1851940
|View full text |Cite
|
Sign up to set email alerts
|

The outer-membrane protein MafA of Neisseria meningitidis constitutes a novel protein secretion pathway specific for the fratricide protein MafB

Abstract: MafB proteins are toxins secreted by Neisseria spp. which are involved in interbacterial competition. Their secretion mechanism has so far not been elucidated. Each strain can produce several MafB variants. On the chromosome, the mafB genes are localized on genomic islands also containing mafA genes. MafA proteins have a role in virulence with reported activities in adhesion and transcytosis of pathogenic Neisseria, a priori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In particular, ST 225 was characterized by the presence of MafB, a toxin for the defense against other bacteria, as well as a protein of the Sel1 repeat family, which plays an important role in iron metabolism. For type 807, the mafA gene, whose expression products are involved in virulence, adhesion and transcytosis in pathogenic Neisseria and are necessary for the function of MafB (Arenas et al, 2020), was notable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, ST 225 was characterized by the presence of MafB, a toxin for the defense against other bacteria, as well as a protein of the Sel1 repeat family, which plays an important role in iron metabolism. For type 807, the mafA gene, whose expression products are involved in virulence, adhesion and transcytosis in pathogenic Neisseria and are necessary for the function of MafB (Arenas et al, 2020), was notable.…”
Section: Discussionmentioning
confidence: 99%
“…The genes specific to ST 807 included a gene encoding the multiple adhesin family protein MafA, whose expression products are involved in virulence, adhesion and transcytosis in pathogenic Neisseria and are required for the function of the polymorphic toxin MafB (Arenas et al, 2020); a gene encoding a protein of the ComF family and required for transformation (Tribble et al, 2012); an M48 family metallopeptidase gene; a gene encoding a protein of the thermonuclease family belonging to the replication, recombination and repair system; a gene encoding the modification methylase ModA (restrictionmodification system); which is involved in the control of phase variations in representatives of the Neisseria genus (Gawthorne et al, 2012); and a gene encoding an AAA family ATPase that may act as a toxin for a type IV toxin-antitoxin resistance system (Yamamoto et al, 2009). We also identified a number of specific genes that constituted the GGI, in particular, traG, eppA, and ych1, in which alterations or lesions have occurred (premature stop codons or reading frameshifts).…”
Section: Genomic Comparison Of Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…TpsA induces persister formation upon direct contact with cells lacking sufficient levels of immunity protein [179]. Very likely, more recently discovered secretion systems that deliver toxins to the target cells [180,181] also contribute to biofilm formation and recalcitrance, a research area that needs to be addressed.…”
Section: Interbacterial Communicationmentioning
confidence: 99%
“…Original observations that MafB could be detected in culture supernatants in the absence of a MafA led to speculation that the toxins may be secreted by association with outer membrane vesicles (Jamet et al, 2015). A later study revealed that MafA mediates MafB translocation across the outer membrane, and after secretion MafB can undergo further maturation via auto-proteolysis of a HINT domain (Arenas et al, 2020). In contrast, the path of entry of secreted toxins into target cells is poorly understood and merits further study.…”
Section: Polymorphic Toxins and Their Deliverymentioning
confidence: 99%